Engineering method of calculation of kinematic parameters of pneumatic impact unit with built-in tank - Атаманов, Юрий Леонидович; Крутиков, Геннадий Анатолиевич; Стрижак, Марьяна Георгиевна (Eastern-European Journal of Enterprise Technologies, 2013)
The method of engineering calculation of impact parameters (maximum speed and coordinates of its realization) of high-speed pneumatic unit with built-in tank is set forth in the paper. The method is based on the method of nonlinear mathematical model rationing with minimum number of dynamic similarity criteria. A number of assumptions allowed obtaining the solutions of differential equations in a dimensionless form as an analytical dependence of maximum value of impact velocity of the piston coordinate, in which the velocity is realized, on dynamic similarity criteria of pneumatic unit. Based on this, the diagrams of velocity and coordinate dependence on the similarity criteria were developed, which cover the whole domain of existence of pneumatic impact units with built-in tank and allow calculations without using a PC. An example of calculation is given.